PERAN BRAND EQUITY DALAM MEMEDIASI PENGARUH INFLUENCER MARKETING DAN DAYA BELI TERHADAP KEPUTUSAN PEMBELIAN - Sunariani, Ni Nyoman; Ratih Ardianti, Putu Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The Covid-19 pandemic has had a major impact on the high use of the internet to access social media which indirectly brings new phenomena or new lifestyles among people in Indonesia, especially in the selection of body care products. Social media platforms are increasingly important in influencing several elements of customer behavior, such as awareness, information acquisition, attitudes, buying behavior, communication, and post-purchase judgments. Research from Data Report also shows data on the number of Indonesian social media users reaching 191.4 million in January 2022. In this study, data were collected through 170 respondents. Data analysis was performed using SEM-PLS. The research results show that influencer marketing, brand equity and purchasing power have an effect on purchasing decisions. Purchasing power affects brand equity. Meanwhile, influencer marketing has no effect on brand equity. Brand equity is able to mediate the influence of purchasing power on purchasing decisions. Meanwhile, brand equity is not able to mediate the influence of influencer marketing on purchasing decisions. Digital marketing is really needed in a world that is now starting to go digital, especially in building brand equity.